1994
DOI: 10.1136/gut.35.9.1275
|View full text |Cite
|
Sign up to set email alerts
|

Diverting colostomy induces mucosal and muscular atrophy in rat distal colon.

Abstract: The progress of adaptive changes in the left colon after diverting colostomy was studied in rats using stereological techniques. Standardised segments of left colon proximal and distal to the colostomy was examined after 0, 1, 2, 4, or 12 weeks. In excluded colon the mucosal weight was reduced by 37% (p<0-01) and the luminal surface area by 47% (p<0.01) after four weeks and reached a steady state at this point of time, as no further reduction was seen from 4 to 12 weeks. The number of proliferating crypt cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
2
8

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 19 publications
1
43
2
8
Order By: Relevance
“…After the twelfth week, the thickness of this layer returned to values close to the six weeks values. These findings were in agreement with those of Kissmeyer-Nielsen et al 15 who found a 34% reduction in mucosal muscle layer weight after twelve weeks of intestinal deviation. In the present study it was not possible to demonstrate a linear correlation between the duration of exclusion and modifications to the thickness of the mucosal muscle layer.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…After the twelfth week, the thickness of this layer returned to values close to the six weeks values. These findings were in agreement with those of Kissmeyer-Nielsen et al 15 who found a 34% reduction in mucosal muscle layer weight after twelve weeks of intestinal deviation. In the present study it was not possible to demonstrate a linear correlation between the duration of exclusion and modifications to the thickness of the mucosal muscle layer.…”
Section: Discussionsupporting
confidence: 83%
“…They also observed that, in the segments without transit, the partial volume of the mucosa was significantly smaller in the group with deviation than in the control group. Kissmeyer-Nielsen et al 15 found that there were significant reductions in the weight of the colon mucosa, by 10% after one week, 21% after two weeks, 37% after four weeks and 31% after twelve weeks of intestinal transit exclusion. They observed that the atrophy of the mucosal layer reached significant levels two weeks after the deviation and reached a peak four weeks after the deviation, stabilizing thereafter 14 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations